Convergent evolution led ribosome inactivating proteins to interact with ribosomal stalk - Lapadula, Walter Jesús (2012)
Ribosome-inactivating proteins (RIPs) inhibit protein synthesis by depurinating an adenine on the sarcin–ricin loop (SRL) of the large subunit ribosomal RNA. Several RIPs interact with the C-terminal end of ribosomal stalk P proteins, and this interaction is required for their full activity. In contrast, the activity of Pokeweed Antiviral Protein is not affected by blocking this stalk component. Here, we provide evidence from phylogenetic analyses and sequence alignments suggesting that the interaction with the C-terminal end of P proteins evolved independently in different RIPs by convergent evolution.